The responsibility of news organizations in the use of algorithms - David Parra; Concha Edo; Almudena Rodríguez (Netcom)
The information industry began to use algorithms in its production processes as a result of the generalization of this kind of tools in the large corporations dominating the current digital economy ; and in the areas of content search, social networks or electronic commerce. This research examines the process of gradual implementation of this technology in Spanish cybermedia through the analysis of the four that have the largest number of unique visitors on its website. The aspects related to the application of algorithms in the distribution and generation of content and in the relationship with audiences and advertisers is examined.